Teaching Methods in Architectural Design Basics - Saghafi, Mahmoud Reza; Mozaffar, Farhang; Moosavi, Seyed Mohsen; Fathi, Noosheen (Ciência e Natura, 2015)
During its changes, architecture teaching, bump into several concerns from initial academic teaching up to nowand it always tolerates some of them permanently. During recent years, many researches went through thatactions with regard to the content debate and organizing architectural teaching. In this present article, we bestshot to go one-step forward in order to solve one of the problems teacher hit upon through method expression andconsideration of teaching method for Architectural Design Basics Courses. Some of these issues for investigationinclude, which goals nail down Architectural Design Basics Courses in university teaching system in Iran?What are the methods and approaches for teaching these courses? Which factors shall investigated beforestarting class session? Which factors are effective on learning process? According to methodology, we started todo research through observation and gathering poll of three universities holding three levels of teaching record inarchitecture (University of Tehran, Marlik Institute of Higher Education and FakhrRazi Institute of HigherEducation), we out –and- out ideas of students and professors of these courses. In addition, through introducingmethods to teach architecture lessons which investigated by researchers during recent years, we will put forwardfor solutions to improve teaching in Architectural Design Basics. In this article, we took advantage fromscanning investigation, we applied observation, library study, and questionnaire to congregate information, andwe brought off quality analysis through a grounded theory approach. In concordance with investigation results,one of the success factors for Architectural Design Basics is dramatize many practices which fired up byprofessors through bring into play different teaching methods.